Atividades hepato e neuroprotetora do dietil-2-fenil-2-telurofenil vinilfosfonato - Ávila, Daiana Silva de (2009)
Despite the growing use of organotellurium compounds in the chemistry and biochemistry field, little is known about the pharmacology of these compounds. The diethyl-2-phenyl-2-tellurophenyl vinylphosphonate (DPTVP) is a vinylic telluride wich shows low toxicity in mice and a high antioxidant activity in vitro. These previous data encoraged us to evaluate the antioxidant potential and the pharmacological benefits that the compound could provide. It was observed that the compound can protect at low concentrations (from 1μM) against the increased lipid peroxidation in brain induced by the neurotoxic agents sodium nitropruside (SNP) and quinolinic acid (QA) in vitro. Furthermore, DPTVP also protected against the mitochondrial dysfunction induced by SNP in cortex, hippocampus and striatum of rats. Besides, the compound did not show neurotoxic effect, once it did not altered mitochondrial viability and neither the glutamatergic system in vitro at the antioxidant concentrations (until 50μM). Considering the possible neuroprotective effect of DPTVP in vitro, the model of Mn neurotoxicity in rats was used in order to evaluate it in vivo and ex vivo. The exposure to Mn for 4 months (137mg/Kg) caused an impairment of the exploratory and motor activity of the rats, as well as alterations in the biochemical parameter analyzed, such as increase in the lipid peroxidation and reduction in the mitochondrial viability and in the [3H] glutamate uptake in striatum, allied to increase in the Mn levels in this brain structure. The treatment for two weeks with DPTVP partially recoved from the neurobehavioral alterations, probably due to the protective effect against the oxidative damage caused by Mn in the striatum observed post mortem. Nevertheless, the animals treated with DPTVP did not showed increased levels of Mn in their striatum, indicating that the compound can act not only as an antioxidant against manganism, but can also impairs the influx or facilitates Mn efflux in thia area. The hepatoprotective activity of DPTVP was also verified against the acetaminophen (APAP) in mice. Both APAP does (200 and 300mg/Kg) caused hepatic alterations sucs as non-proteic SH depletion, Increase in TBARS levels, inhibition of δ- ALA D, ALT leakage and morphologic damage to the hepatocytes, nevertheless at different intensities. Hence, The treatment with DPTVP (30, 50 and 100μmol/Kg) showed effectiveness when the APAP dose preadministeres was 200mg/Kg. Against the dose of 300mg/Kg, the compound has just recovered from the histomorphologic alterations to hepatocytes. The present estudy has also evidenced that the antioxidant activity depicted by the vinilc telluride is due to its scavenger activity, once the compound was able to neutralize reative oxygen (ROS) and reactive nitrogen species (RNS), such as H2O2, OH , ON and ONOO-, probably due to the formation of telluroxide, which is due to the molecular structure of the compound. Taken together, these results suggest that DPTVP has neuro and hepatoprotective actions at low doses probably due to its strong antioxidant activity and that the formation of telluroxide is very important to these effects.